Docentes de IPES de São Paulo em tempos de precarização das relações de trabalho e mercantilização do ensino - Oliveira, Débora Lessa de Azevedo Corrêa de (2014)
The study of the precarization of the professors work relations is meaningful since it enables us to connect education and work, two fundamental axes for the comprehension of our society and its inequalities. In this essay, we focus on the case of the professors in private institutions of higher education - IPES - of São Paulo. The process of the work precarization in the IPES is a reflex of three important changes: 1) Transformations on the factories manufacturing floor with the development of Taylorism/ Fordism and Toyotism during the XX century; 2) Structural and policy changes on Brazilian high education system, mainly from the middle of the aforementioned century to nowadays; 3)Consolidation of neoliberalism. The expansion of the IPES carries a potential contradiction insofar as it submits a wide contingent of critical thinking workers to what we could call a university despotism at the same time that it promises millions of students practically unatainable career prospects. These contradictions have not yet become apparent so far, but there is a high possibility that they will become a reality in the near future